Parallel texts from the Swedish Migration Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded with "w3m -dump" from an ubuntu shell, from the website of the Swedish Migration Agency.

The texts have been downloaded using the command 'w3m -dump' from an ubuntu shell, whereafter the resulting text files were stripped to contain only the interesting text (no menus and such).

Parallella texter nedladdade med hjälp av "w3m -dump" från ett ubuntu-skal, ifrån Migrationsverkets webbplats.

Texterna har laddats ner med hjälp av kommando 'w3m -dump' ifrån ett ubuntu-skal, varpå resulterande textfiler har skalats av till att innehålla endast den intressanta texten (inga menyer och dylikt).
Parallella texter från Migrationsverket
Keywords: immigration policy; invandringspolitik; Emigration and Immigration; Utvandring och invandring; Legislation and legal systems; Lagstiftning och rättssystem; International politics and organisations; Internationell politik och organisationer; Conflict, security and peace; Konflikter, säkerhet och fred; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur